PENERAPAN MANAJEMEN PROYEK PADA INOVASI PRODUK “PUPUK TULANG ORGANIK (PULANG) - Juriana, Elvi; Ong, Teddy; Vanders, William; Firdiansyah, Ronny (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
The use of pesticide fertilizers in the community environment causes soil pollution.Our business is to make organic bone fertilizer products, with the aim that thisproduct can help the community enjoy plant products that are free from pests andharmful chemicals. The method used is a qualitative method with a descriptiveapproach. By implementing ten project management processes, namely projectintegration, project scope management, project time management, project costmanagement, project quality management, project human resource management,project communication management, project risk management, projectprocurement management, and project stakeholder management, The projectproduces organic bone fertilizer that fertilizes the soil and is low-risk. Theimplementation of project management can assist the team in planning, managing,and executing work to meet project requirements on time.